1978
DOI: 10.1083/jcb.78.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potentials and resistances of giant mitochondria. Metabolic dependence and the effects of valinomycin.

Abstract: The membrane potentials and resistances of giant mitochondria from mice fed cuprizone have been studied. They were found to correspond approx. 10-20 mV, positive inside, and 2 M~, respectively. These properties were found to be independent of the metabolic state. The microelectrodes were in the inner mitochondrial space since (a) the potentials in the presence of valinomycin depended on the K § concentration of the medium and the magnitude of the K § diffusion potentials was consistent with the presence of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 37 publications
4
5
0
Order By: Relevance
“…As shown in Tables I1 and IV, the metabolic state and the presence or absence of inhibitors had no effect on the membrane potential (E) or the resistance (R), in agreement with our previous results (14,15). Therefore, no metabolic dependence of the mitochondrial membrane potential can be demonstrated.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As shown in Tables I1 and IV, the metabolic state and the presence or absence of inhibitors had no effect on the membrane potential (E) or the resistance (R), in agreement with our previous results (14,15). Therefore, no metabolic dependence of the mitochondrial membrane potential can be demonstrated.…”
Section: Resultssupporting
confidence: 91%
“…In interpretation that the impaled mitochondria are functional since they accumulate calcium salts in the appropriate medium and, in addition, they phosphorylate ADP to ATP which causes myofibrillar contraction. Our accompanying paper (15) presents evidence that the microelectrode is in the inside space of the mitochondria since (a) the membrane potential shows the predicted dependence on the external concentration of K § in the presence of valinomycin, (b) the electrical parameters remain unchanged by the removal of the outer membrane and the evagination of the inner mitochondrial membrane, and (c) punch-through experiments, in which the microelectrode traverses through the mitochondrion, reveal a single membrane potential in the presence of valinomycin or under either energized or inhibited conditions. In these and other experiments using the giant mouse mitochondria, the evidence does not support the Mitchell chemiosmotic hypothesis which proposes a direct role of metabolism in the membrane potential and predicts a potential at least one order of magnitude higher and with an opposite sign.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This obviously fed the ongoing discussion. Tedeschi and co-workers responded to criticism with some brilliant experiments, employing now giant mitochondria obtained from the livers of cuprizone-fed mice [11][12][13][14][15]. They showed that myofibrils adjacent to impaled mitochondria supplied with ADP would contract, thus indicating the production of ATP.…”
Section: The Dawn Of Mitochondrial Electrophysiologymentioning
confidence: 99%